Respuesta :

Step-by-step explanation:

So in the equation given, y = 2x - 3

you substitute x for whats given in the table in the x column.

Example

In the graph the first number under the x colum is -1.

y = 2x - 3 in the equation you take out x and put -1.

So now the equation becomes y = 2 × -1 - 3.

Using bedmas to solve the question you should get -5

Which now means y = -5

To plot the point now x would be -1 and y would be -5 (-1, -5)

Same thing for the second number in the x Column.

y = 2 × 1 - 3 which equals -1

To plot it

x = 1 y = -1. (1, -1)

And for the last number 3.

Agai. You substitute x for 3 which makes the equation y = 2 × 3 - 3

this gives you 3 and to plot it

x would be 3 and y would be 3